(untitled) (Hoboken, N.J., 2006)
Emergent Information Technologies and Enabling Policies for Counter-Terrorism provides a unique, integrated treatment of cutting-edge counter-terrorism technologies and their corresponding policy options. Featuring contributions from nationally recognized authorities and experts, this book brings together a diverse knowledge base for those charged with protecting our nation from terrorist attacks while preserving our civil liberties.
Keywords: Terrorism,Terrorism,Terrorism,Information technology,Khủng bố,Khủng bố,Khủng bố,Công nghệ thông tin; Prevention,Government policy,Technological innovations,Government policy,Phòng chóng,Chính sách của chính phủ,Đổi mới công nghệ,Chính sách của chính phủ; United States,United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ